Submorphemic iconicity in the lexicon: a diachronic approach to English ‘gn- words’ - Dennis Philps (Lexis: Journal in English Lexicology)
By applying a principle of submorphemic invariance to the word-initial segment gn- (phonologically /n/) in the heuristic class of English ‘gn- words’, I show that this segment functions as a ‘sublexical marker’ (), defined as a semiologically and notionally invariant submorphemic unit within the subset(s) of words of which it is a formative. I go on to claim, based on evidence provided by phononotional GN-/GVN(-) alternation, that although must be considered as structurally indivisible in Modern English, in may originally have functioned as a ‘core invariant’ and as a variable in the pre-history of English, specifically in Proto-Indo-European. Analysing gn- in most ‘gn- words’ of Anglo-Saxon origin and some of Greek origin as the surface trace of an underlying notional domain linked to jaw-related phenomena (sound articulation, mastication, manducation, etc.) suggests that there exists an extralinguistically motivated, causal relation between and this domain involving the concept of ‘submorphemic iconicity’.